Developing Developing an English Supplementary Book Using Project-Based Learning for 11TH grade Students - Mutyara Nur Robi'ah; Istina Atul Makrifah; Siti Rofi'ah (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2024)
Students find it difficult to obtain material due to the lack of learning facilities and media, therefore students and teacher need media that can be used that contains a summary of English learning materials so that learning can be delivered. One of the learning tools that can be used in the second semester 11th grade is English supplementary book. This book contains a summary of the material as well as there are practice questions and explanations of various materials with hope students will be able to develop knowledge, skills, and attitudes. Supplementary reading materials in English course programs can be applied to give students a comprehensive knowledge of the subject matter based on the national standard that they cannot get in their regular class (endang nuryasana, 2020). The English Supplementary Book has been validated by the media validator and the material validator, each of which has a score of 94% and 84%. The media also received a good response from students, namely 73% which means